Dynamic orthognathic surgical procedure (DOSP) in asymmetric maxillomandibular dysmorphism secondary to unilateral micrognathia: Outcomes of 12 consecutive cases. Issue 2 (February 2021) - Morice, A.; Galliani, E.; Kadlub, N.; Tomat, C.; Vazquez, M.P.; Picard, A.; Diner, P.A.
Abstract: This study aimed to evaluate the outcomes following a dynamic orthognathic surgical procedure performed at the end of growth to treat asymmetric maxillomandibular deformities linked to unilateral micrognathia when conventional orthognathic surgery was not feasible. The dynamic orthognathic surgical procedure (DOSP) combined concomitant mandibular distraction osteogenesis with contralateral poorly stabilized sagittal split osteotomy and Le Fort I osteotomy. Cephalometric studies were retrospectively conducted on pre- and postoperative lateral and frontal cephalographs, and maxillomandibular movements were calculated. Outcome scores were computed by both experts and laypersons based on photographic analyses. There was a significant postoperative increase in height of the micrognathic ramus in all patients ( n = 12; p = 0.002). The angle between the occlusal cant and horizontal reference plane decreased significantly in all of the patients, as did the angle between the midline sagittal plane and mandibular tilt ( p < 0.001). Postoperative outcome scores showed significant improvements in all cases, according to both expert and layperson groups. This procedure allows correction of maxillomandibular asymmetries linked to micrognathia. However, it cannot resolve all the factors participating in facial asymmetry, such as those originating in the oculo-auriculo-ventricular spectrum or complex tumor sequelae, and second-step procedures may be required.